Merger, Akuisisi, dan LBO sebagai Instrumen Restrukturisasi Keuangan: Analisis Literatur Terkini - Muchammad Mujib; Lumhatus Shofi Sa`adah; Aprilia Wulandari; Waris Adi Darmawan; Ridho Hafiz Maulana; Achmad Candra Irawan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Finansial restructuring is an important strategy in maintaining company sustainability and growth, especially in the face of external and internal pressures. Mergers, acquisitions, and leveraged buyouts (LBOs) are the three main instruments in restructuring strategies used by companies in various sectors. This study aims to systematically review the current academic literature on the impact, challenges, and effectiveness of using mergers, acquisitions, and LBOs in the context of financial restructuring. By reviewing more than 20 sources from academic journals and recent financial reports, this study identifies trends, research gaps, as well as theoretical and practical contributions of each of these instruments. The findings show that all three instruments have significant potential to improve a firm's operational efficiency and capital structure, but also carry substantial risks if not managed strategically.